Effective practices in AI literacy education : case studies and reflections - O'Dea, Xianghan; Ng, Davy Tsz Kit (Emerald points., 2024)
The rapid adoption of Artificial Intelligence in various industries and the emergence of Generative Artificial Intelligence (GenAI) in recent years have prompted highlighted interest in training and supporting university students to develop industry-oriented AI literacy competencies. Effective Practices in AI Literacy Education serves as a go to guide for university key stakeholders, such as students, academics and professional support staff seeking to develop their AI literacy skills. Chapters provides the reader with applicable strategies and evidence-based practices through a comprehensive collection of international higher education case studies. The case studies offer innovative approaches in teaching AI literacy in a broad spectrum, and discipline specific approaches. Each case study is also complemented by the contributors' own reflections. The intention is to promote deeper engagement and critical thinking. Effective Practices in AI Literacy Education sheds light on an under explored topic and helps the reader acquire a deeper understanding of the topic of current interest - AI literacy Education in higher education. It offers practical guidance and innovative solutions in this area through showcasing impactful case studies.